Use of an in vitro gas production method to study kinetics of rumen dry matter degradation of forages - Dhanoa, M.S.; Tanner, J.C.; Owen, E.; Theodorou, M.K.; Winugroho, H.M. (Cambridge University Press, 1998)
In addition to assessing rate and extent of gas production from fermenting forages in vitro with rumen micro-organisms, gas production methods (e.g. Theodorou et at, 1994) may be used also to study the degradation kinetics of forage dry matter and its fractions. As the substrate dry matter can be lost only through fermentation or solution, this removes the error inherent in the polyester bag method caused by fine particle losses from bags being deemed part of the ‘soluble’ fraction. The pressure transducer technique (PTT) of Theodorou et al. (1994) was used to measure gas production from nine tropical forage samples (Table 1). Nine bottles were prepared from each of the forage samples. Two bottles of each forage were harvested after 8, 24 and 48 h of incubation and a further three bottles at 72 h, to determine dry matter (DM) and organic matter (OM) losses. The same nine forages were assessed using the polyester bag method (Mehrez and Ørskov, 1977) to obtain DM and OM disappearance after rumen incubations of 4, 8, 24, 48 and 72 h. The soluble fraction was determined by hand washing. The reproducibility of measured losses, at given times, was examined using concordance (rc ) correlation (Lin, 1989) and mean square prediction error (MSPE, Bibby and Toutenberg, 1977). Also the simple exponential model was used to estimate the fractional rate of DM degradation (kd ) and asymptote A (%) for each forage and the values obtained using PTT (kd,ptt ) and in situ (kd,bag) compared using rc and MSPE.